Cabaran Dalam Pemuliharaan Bangunan Istana Lama Seri Menanti Di Negeri Sembilan - Masrom, Md. Asrul Nasid; Abdul Kadir, Zulhaida (Research in Management of Technology and Business, 2020)
The heritage building conservation project is one of the national treasure conservation measures that is gaining attention. Lack of conservation work can cause heritage buildings to suffer damage or destruction. Several problems have been identified as contributing factors to heritage building conservation projects receiving less attention. Among them are the lack of experts, the difficulty of obtaining equivalent spare parts and the lack of original reference sources or documentation. However, this problem still lacks attention among professionals. Therefore, this study identifies the problems that occur during the conservation project of Istana Lama Seri Menanti building is implemented, as well as the conservation process used and the impact on the building of Istana Lama Sri Menanti. This study used the interview method which directly involves four parties participated in the conservation project of Istana Lama Sri Menanti building, namely, the management of Istana Lama Seri Menanti, contractors and two consultants as project advisors from public universities. The information obtained from the interviews conducted has achieved the objectives of this study. Therefore, it is hoped that this study can be used as a reference for problem solving that occurs during the process of conservation of historic buildings as well as a reference for relevant research in the future.